Spatial and temporal trends in the ecological risk posed by polycyclic aromatic hydrocarbons in Mediterranean Sea sediments using large-scale monitoring data. (October 2021) - Rizzi, C.; Villa, S.; Chimera, C.; Finizio, A.; Monti, G.S.
Highlights: Polycyclic aromatic hydrocarbons concentrations in Mediterranean Sea sediments. Primary origin of contamination from biomass burning. Different relative abundances among the Mediterranean basins. Unacceptable risk for benthic organisms in Western basin, decreasing west-east. Abstract: Benthic organisms play an important role in aquatic ecosystems and are often used as indicators of toxic environments. In this study, we reconstructed the spatial and temporal trend of risk to benthic communities living in sediments of the Mediterranean Sea posed by the presence of 16 polycyclic aromatic hydrocarbons (PAHs). Moreover, the origins of PAH contamination in the sea were also investigated. The analysis included multiple steps, starting with an in-depth review of available studies (from the early 1980s to 2019) reporting PAH concentrations in sediments of the Mediterranean Sea. Subsequently, the collected data were spatialised and clustered according to the four basins of the Mediterranean as defined by the Mediterranean Strategy on Sustainable Development and the United Nations Environment Programme Mediterranean Action Plan. We employed additive models, a flexible and versatile tool for coping with non-linear trends by means of smooth functions, to estimate temporal trends in PAH concentrations. Finally, the primary origins of contamination and temporal trends in ecological risk were determined using a combination of approaches. The results indicated that PAHs in Mediterranean sediments originate primarily from biomass burning, with a contribution from combustion of coal and liquid fossil fuels, the latter being representative of sites near urban centres or harbours. A significant positive correlation between annual growth rates of PAH concentration in sediment and wildfires was found. The estimated non-linear trends of concentrations and risk showed different temporal patterns across basins. In recent years, especially in the Western Mediterranean, the estimated trends suggest PAH concentrations are posing an increasing risk. These results indicate the need for stronger efforts to achieve the objectives of the Marine Strategy Framework Directive.